The impact of the centralized system of governance on the development trajectory of Tsholotsho rural district council - Moyo, Nkosilondile (Midlands State University, 2019)
The thrust of this research is to show how the centralized system of governance has greatly impacted on the development trajectory of Tsholotsho Rural District Council. It identifies the components of the centralized system of governance characterised by the lack of decision making powers, lack of citizen participation in the both decision making and development processes and the centralised policy making powers which are castigated down to local authorities to implement. The top-down approach in these processes greatly impacts the development of the local authorities. Interviews, focus group discussions and structured interviews were used in collection of data from respondents. These methods were helpful in coming up with the relevant information in regard to the centralized system of government and how it impacts on development of Tsholotsho as a whole. The research findings were interpreted and analysed with the aid of pie charts and bar graphs in order to clearly present the data. The research findings clearly show that the centralized system of governance has a great impact in term of development in that issues to do with funding are controlled by the central government. Funding and decision making are the cornerstone for development to take place as a result central government is seen as impinging on the development of the areas through constant interference on the day to day running of local authorities